Multilayer Thin Films Versatile Applications for Materials Engineering - Basu, Sukumar (IntechOpen, 2020)
This book, "Multilayer Thin Films-Versatile Applications for Materials Engineering", includes thirteen chapters related to the preparations, characterizations, and applications in the modern research of materials engineering. The evaluation of nanomaterials in the form of different shapes, sizes, and volumes needed for utilization in different kinds of gadgets and devices. Since the recently developed two-dimensional carbon materials are proving to be immensely important for new configurations in the miniature scale in the modern technology, it is imperative to innovate various atomic and molecular arrangements for the modifications of structural properties.
Description based on print version record.
IntechOpen Engineering 2019 - 2021
Keywords: Technology & Engineering / Materials Science; Technology; Electronic books